We Are Part of the Ecosystem. Therapeutic work within communities of practice - Emily Salja; Evren Salja (Murmurations)
As practitioners, we often share community memberships with those who consult us. We practice from a place of familiarity with how Western psychotherapy has failed, oppressed, and blamed racialised, neurodiverse, 2SLGBTQIA+, disabled, and otherwise marginalized people. Some is lived experience, the rest we draw from community knowledges. We hope to contribute a response to the question, “What can it mean to intentionally build a therapeutic practice outside the expectations of clinical professionalism as a person, practitioner, and community member?” Or, from another angle: "What does it mean to be a part of the ecosystem we support?" Our experiences and observations are framed by privileges (whiteness, stable housing, access to academic spaces, healthcare, and transport) and marginalisations that inform and contextualize this work. In perpetuity, we acknowledge and honour the brilliance and labour of Kimberly Crenshaw, Leah Lakshmi Piepzna-Samarasinha, Robin Wall Kimmerer, and countless other BIPOC scholars, activists, writers and beyond who have defined and created intersectional (Crenshaw, 1989) systems of resistance and survival. Any errors in the interpretation of these bodies of work are our own.